Alimentación de terneros Brown Swiss con cuatro concentrados comerciales más forraje. - Espinoza Coronel, Jhorghi Franklin (2009)
The meat of bovine is a product of massive consumption in the national and international markets, it represents for our producers a very important activity from the economic point of view considering that in our mean the traditional form of upbringing of calves is used, that is to say with the help of milk for lingering periods of time, representing this a deficit in the revenues of the producer, reason for which this investigation was executed, being our main objective to evaluate the use of four concentrate more forage in the feeding of calves Brown Swiss, to determine the effect of the same envelope the production of weight and meat development, being used the following concentrate for each treatment: T1 Grass + Balanced Pronaca, T2 Pasture + Balanced Nutril, T3 Pasture + Balanced alibaec, T4 Grass + Balanced UTEQ. This work was executed in the program of Bovine of Milk and Meat of the experimental property Maria of property of the Technical State University of Quevedo, located in the Km 7 ½ of the road Quevedo – the Connection, county of Rios, The investigation had a duration of 84 days. 12 calves Brown Swiss was used with an approximate weight of 65 – 184 Kg, and with an age average of 2 - 6 months. The design of blocks was used at random in (DBCA) factorial arrangement 4 x 4 four types of having balanced by four periods with three repetitions, to determine differences among stockings of treatments, they were compared using the test of multiple ranges of (Tukey (P≥ 0,05) The variables in study were: food consumption, gain of weight, nutritious conversion and economic analysis. The results were the biggest food consumption based on matter he/ she dries off he/she obtained with Balanced alibaec (117,28 total Kg). with the one balanced of UTEQ the best gain of weight (55.80 Kg) was obtained. The nutritious most efficient conversion reported it Balanced UTEQ (2.42). The best relationship benefits cost he/she met with the treatment Nutril (0,37 USD).